(untitled) (Research, Society and Development, 2020)
Breast milk acts in the prevention and control of morbidities in childhood and adulthood, being essential for the protection and health promotion of infants, influencing biological and emotionally in their growth and development. However, many mothers prefer to promote early weaning and several may be the factors that influence the genesis of this event. Given the above, the aim of the study is to perform a bibliographic search on the factors that influence early weaning. This is an integrative literature review. To search and select studies, the following databases were used: Pubmed, Scielo and Virtual Health Library-VHL, after applying the inclusion and exclusion criteria, 15 studies were selected, which were published between the years 2015 to 2019. Having exposed the results and the articulation between the contents of the selected scientific papers, we noticed There are a variety of factors related to breastfeeding discontinuation. In the present study, there was a greater emphasis on the mother’s return to work, the myth of weak and / or insufficient milk, as well as low education, maternal age and nipple trauma. It is concluded that it is necessary to work on public health policies aimed at preventing early weaning, individual and collective health education during prenatal care, and monitoring of nursing mothers by the health team throughout the lactation process.